Dexmedetomidine and Fentanyl Exhibit Temperature Dependent Effects on Human Respiratory Cilia - Welchering, Nils; Ochoa, Sebastian; Tian, Xin; Francis, Richard; Zahid, Maliha; Muñoz, Ricardo; Lo, Cecilia W. (Frontiers in Pediatrics, 2015)
Background: Dexmedetomidine (dex) is commonly used in intensive care due to its effective sedation and analgesia with few adverse effects and minimal respiratory depression. However, we recently observed that exposing mouse epithelial respiratory cells to dex decreased ciliary beat frequency (CBF), suggesting dex may pose pulmonary risk. Objective: The purpose of this study is to determine the effects of this drug on CBF in human respiratory epithelia. Methods: Human nasal epithelial cilia were obtained from the inferior nasal turbinate with a rhinoprobe and placed in culture medium at 15º and 37°C. At 5 and 30 minutes, videomicroscopy was used to assess CBF, either without (control) or with different concentrations (1nM, 5nM, 10nM) of dex, fentanyl, and dex+fentanyl combination. Results: At 15°, CBF was lower in the dex group compared to controls at 5 and 30 minutes. At 37°, there was a significant increase in CBF with dex at 5 and 30 minutes, except for dex at 5nM after 5 minutes which showed a significant decrease. At 15°C the combination of dex+fentanyl (fen) showed a positive interaction, causing less ciliary inhibition as expected. In contrast, no interaction between drugs was seen between dex and fen at 37°C. Conclusion: At low temperatures, dex reduces CBF in human respiratory epithelia, whereas dex increases CBF at physiologic temperature in vitro. Whether these effects translate into clinical consequences during hypothermia, as with cardiopulmonary bypass surgery will require further studies.